embelajaran Example Non Example terhadap Hasil Belajar IPA Siswa Kelas V - Sartika, Leni; Satinem, S; Yuneti, Armi (Faktor : Jurnal Ilmiah Kependidikan, 2023)
This study aims to determine the completion of science learning outcomes for fifth grade students of SD Negeri 2 Air Satan. The research method used is a quasi-experimental. The population is all fifth grade students of SD Negeri 2 Air Satan and the research sample is 14 students. Data was collected by using saturated sampling technique. The data collected through the test was then analyzed using the z test. Based on the results of data analysis with a confidence level of = 5% and dk = 13, it shows that zcount = 2.89 and ztable = 1.64 (zcount> ztable). Thus, it can be concluded that the science learning outcomes of fifth grade students of SD Negeri 2 Air Satan after the implementation of the non-example learning model are significantly completed.